CONSUMER CONSIDERATIONS IN BUYING TEMPE: A CASE STUDY IN SEPANDE VILLAGE, SIDOARJO - Lestari, Putri Indah; Ambarwati, Rita (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
This research aims to determine the influence of price, product quality, and personal selling on consumers' purchasing decisions regarding tempe. This study utilizes a quantitative approach as the research method, employing a questionnaire distributed incidentally. The study involves a sample of 96 individuals who meet the author's criteria, determined using the Lemeshow formula. Quantitative data analysis technique is employed, utilizing statistical methods to analyze the data. The statistical method used is Smart-PLS. Based on the research findings, it was discovered that price has a positive and significant impact on tempe  purchasing decisions in the village of Sepande, Sidoarjo. Product quality has a positive and significant influence on tempe purchasing decisions in the village of Sepande, Sidoarjo. Personal selling has a positive and significant effect on tempe purchasing decisions in the village of  Sepande, Sidoarjo. Furthermore, within this context, price, product quality, and personal selling collectively have a significant impact on tempe  purchasing decisions in the village of Sepande, Sidoarjo.